Proceedings of Fourth Annual Large Hadron Collider Physics — PoS(LHCP2016) 2016
DOI: 10.22323/1.276.0007
|View full text |Cite
|
Sign up to set email alerts
|

Status and developments of event generators

Abstract: Event generators play a crucial role in the exploration of LHC physics. This presentation summarizes news and plans for the three general-purpose pp generators Herwig, Pythia and Sherpa, as well as briefer notes on a few other generators. Common themes, such as the matching and merging between matrix elements and parton showers, are highlighted. Other topics include a historical introduction, from the Lund perspective, and comments on the role of MCnet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 167 publications
(190 reference statements)
0
12
0
Order By: Relevance
“…Instead, we employ the approach developed in [27,67]. Following this approach, first a kernel A b a x , µ 2 is determined from the Monte Carlo solution of the evolution equation for any initial parton of flavor b evolving to a final parton of flavor a; 5 then, this is folded 5 In practice, since the initial state partons can be only light quarks or gluons, it is enough to determine the kernel A b a only for one initial state quark and a gluon. with the non-perturbative starting distribution A 0,b (x):…”
Section: Fit To Precision Dis Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we employ the approach developed in [27,67]. Following this approach, first a kernel A b a x , µ 2 is determined from the Monte Carlo solution of the evolution equation for any initial parton of flavor b evolving to a final parton of flavor a; 5 then, this is folded 5 In practice, since the initial state partons can be only light quarks or gluons, it is enough to determine the kernel A b a only for one initial state quark and a gluon. with the non-perturbative starting distribution A 0,b (x):…”
Section: Fit To Precision Dis Datamentioning
confidence: 99%
“…While great progress has been achieved in the last decade on matching and merging methods [5][6][7] to combine parton showers with perturbative calculations through next-to-leading order (NLO), important open questions still remain, both conceptual and technical, on the appropriate use of parton distribution functions in parton showers (see e.g. [8][9][10][11]) and on the treatment of the shower's transverse momentum kinematics (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Deductor starts with the Born matrix elements for two jet production. It would, of course, be best to put in the right NLO matrix elements and subtractions to make the shower cross section match the NLO jet cross section [57,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. In principle, this is straightforward in the Deductor framework [4].…”
Section: A One Jet Inclusive Cross Sectionmentioning
confidence: 99%
“…The successor programs [1][2][3][17][18][19][20][21][22][23], are quite sophisticated. Useful reviews of the field can be found in [24,25]. One of the available successor programs is our own, Deductor [15,21,[26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%